Controller design for two-wheels inverted pendulum vehicle using PISMC - Nawawi, S. W.; Ahmad, M. N.; Osman, J. H. S.; Husain, A. R. (2006)
The research on two-wheel inverted pendulum or commonly call balancing robot has gained momentum over the last decade at research, industrial and hobby level around the world. This paper deals with the modeling of 2- wheels Inverted Pendulum and the design of Proportional Integral Sliding Mode Control (PISMC) for the system. The mathematical model of 2-wheels inverted pendulum system which is highly nonlinear is derived. The final model is then represented in state-space. A robust controller based on Sliding Mode Control is proposed to perform the robust stabilization and disturbance rejection of the system. A computer simulation study is carried out to access the performance of the proposed control law.